A Protocol for Improved Precision and Increased Confidence in Nanoparticle Tracking Analysis Concentration Measurements between 50 and 120 nm in Biological Fluids - Parsons, Martin E. M.; McParland, Damien; Szklanna, Paulina B.; Guang, Matthew Ho Zhi; O’Connell, Karen; O’Connor, Hugh D.; McGuigan, Christopher; Ní Áinle, Fionnuala; McCann, Amanda; Maguire, Patricia B. (Frontiers in Cardiovascular Medicine, 2017)
Nanoparticle tracking analysis (NTA) can be used to quantitate extracellular vesicles (EVs) in biological samples and is widely considered a useful diagnostic tool to detect disease. However, accurately profiling EVs can be challenging due to their small size and heterogeneity. Here, we aimed to provide a protocol to facilitate high-precision particle quantitation by NTA in plasma, the supernatant of activated purified platelets (the platelet releasate) and in serum, to increase confidence in NTA particle enumeration. The overall variance and the precision of NTA measurements were quantified by root mean square error and relative standard error. Using a bootstrapping approach, we found that increasing video replicates from 5 x 60 sec to 25 x 60 sec captures led to a reduction in overall variance and a reproducible increase in the precision of NTA particle-concentration quantitation for all three biofluids. We then validated our approach in an extended cohort of 32 healthy donors. Our results indicate that for vesicles sized between 50-120nm, the precision of routine NTA measurements in serum, plasma, and platelet releasate can be significantly improved by increasing the number of video replicates captured. Our protocol provides a common platform to statistical compare particle size distribution profiles in the exosomal-vesicle size range across a variety of biofluids and in both healthy donor and patient groups.